Bisphenol A at the reference level counteracts doxorubicin transcriptional effects on cancer related genes in HT29 cells - Delgado, Margarida (2016)
Human exposure to Bisphenol A (BPA) results mainly from ingestion of food and beverages. Information regarding BPA effects on colon cancer, one of the major causes of death in developed countries, is still scarce. Likewise, little is known about BPA drug interactions although its potential role in doxorubicin (DOX) chemoresistance has been suggested. This study aims to assess potential interactions between BPA and DOX on HT29 colon cancer cells. HT29 cell response was evaluated after exposure to BPA, DOX, or co-exposure to both chemicals. Transcriptional analysis of several cancer-associated genes (c-fos, AURKA, p21, bcl-xl and CLU) shows that BPA exposure induces slight up-regulation exclusively of bcl-xl without affecting cell viability. On the other hand, a sub-therapeutic DOX concentration (40 nM) results in highly altered c-fos, bcl-xl, and CLU transcript levels, and this is not affected by co-exposure with BPA. Conversely, DOX at a therapeutic concentration (4 μM) results in distinct and very severe transcriptional alterations of c-fos, AURKA, p21 and CLU that are counteracted by co-exposure with BPA resulting in transcript levels similar to those of control. Co-exposure with BPA slightly decreases apoptosis in relation to DOX 4 μM alone without affecting DOX-induced loss of cell viability. These results suggest that BPA exposure can influence chemotherapy outcomes and therefore emphasize the necessity of a better understanding of BPA interactions with chemotherapeutic agents in the context of risk assessment.